Learning path : enterprise Java development. - Gorman, Brian; Bowersox, Kevin; Kalin, Martin; Graff, Petter; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"The Java Platform, Enterprise Edition (Java EE) is a collection of technologies and APIs for the Java platform designed to support large-scale, distributed, transactional, and highly available applications that support mission-critical business requirements. This Learning Path gives you a hands-on introduction to Java EE 7 and some of the most popular and useful APIs, tools, and services for building applications in Java EE."--Resource description page.
Learning Java EE 7 / Brian Gorman -- Learning Spring programming / Kevin Bowersox -- Building Web services with Java : working with RESTful and SOAP-based services / Martin Kalin -- Hibernate and Java Persistence API (JPA) fundamentals / Kevin Bowersox -- Design patterns in Java / Petter Graff.
Presenters, Brian Gorman, Kevin Bowersox, Martin Kalin, Petter Graff.
Title from resource description page (viewed March 15, 2016).
Keywords: Java (Computer program language); Web site development; Web sites -- Design; Electronic books